(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Total concentration and pollution indices of mercury (Hg), lead (Pb), chromium (Cr), cadmium (Cd), arsenic (As), nickel (Ni), and cobalt (Co) in dumpsite soil located in University of Cross River State, Calabar were evaluated in this work. Soil samples were collected at 0 - 15cm depth from two sampling stations at the dumpsite once in the months of April, August and December, 2021 and analyzed to the closest mg/kg using Atomic Absorption Spectrophotometer (AAS). The concentrations of the heavy metals showed that Cd>Pb>Ni>Cr>As>Co. All the concentrations of the heavy metals examined when compared with those of average value of heavy metals in shale showed that all the metals were lower than their corresponding world average value except Cd. Geoaccumulation index indicated unpolluted to moderately polluted for all metals studied except Cd which indicated strong to very strongly polluted. Contamination factor for Cd indicated very high contamination. Contamination degree for site 1 and 2 indicated considerable degree of contamination and moderate degree of contamination respectively. Pollution load index values investigated were within the baseline level for all the stations. The heavy metal pollution is attributable to the waste deposited at the dumpsite located in the institution. It is recommended that the dumpsite be relocated to another location that is far away from the residential area and from drinking water sources like boreholes.